Efektivitas guided discovey learning dalam model pembelajaran kooperatif tipe student team achevievement division (STAD) ditinjau dari kemampuan penalaran matematika dan self-confidence siswa - Irawati Windani; Safarudin Safarudin (Institut Agama Islam Negeri (IAIN) Bone, 2021)
This study aims to determine whether guided discovery learning in the STAD type of cooperative learning model is effective when viewed from the mathematical reasoning ability and self-confidence of class XI students of SMA Negeri 1 Baubau. This type of research is a quasi-experimental research with the research design used, namely the One-Group Pretest-Posttest Design. Data collection techniques are test and non-test. The research instrument was a test question on mathematical reasoning abilities and a non-test in the form of a questionnaire on students' self-confidence. The data analysis in this research is descriptive analysis and inferential analysis. Before carrying out the hypothesis test, the assumption test is carried out first, it will be tested for normality with a significant level α = 0.5. The results of this study were the pretest mean value of students' mathematical reasoning abilities with guided discovery learning in the STAD cooperative learning model, namely 3.25, an increase in the posttest average score of 8.55. The mean value of the initial questionnaire of students 'self-confidence was 70.38 and in the final questionnaire, the students' self-confidence had increased by 91.45. So it can be concluded that guided discovery learning in the STAD type cooperative learning model is effective in terms of mathematical reasoning abilities, and self-confidence of class XI students of SMA Negeri 1 Baubau.Penelitian ini bertujuan untuk mengetahui apakah guided discovery learning dalam model pembelajaran kooperatif tipe STAD efektif jika ditinjau dari kemampuan penalaran matematika, dan self-confidence siswa kelas XI SMA Negeri 1 Baubau. Jenis penelitian ini adalah penelitian eksperimen semu dengan desain penelitian yang digunakan yaitu yaitu One-Group Pretest-Posttest Design. Teknik pengumpulan data yaitu tes dan non tes. Instrumen penelitian berupa soal tes terhadap kemampuan penalaran matematika dan non tes berupa angket terhadap self-confidence siswa. Analisis data dalam penelitian ini adalah analisis deskriptif dan analisis inferensial. Hasil penelitian ini yaitu nilai rata-rata pretest kemampuan penalaran matematika siswa dengan guided discovery learning dalam model pembelajaran kooperatif tipe STAD yaitu sebesar 3,25 mengalami peningkatan pada nilai rata-rata posttest yaitu sebesar 8,55. Nilai rata-rata angket awal self-confidence siswa yaitu sebesar 70,38 dan pada angket akhir self-confidence siswa mengalami peningkatan yaitu sebesar 91,45. Dapat disimpulkan bahwa guided discovery learning dalam model pembelajaran kooperatif tipe STAD efektif ditinjau dari kemampuan penalaran matematika, dan self-confidence siswa kelas XI SMA Negeri 1 Baubau.